ELECTRE-TRI multicriteria approach for measuring performance of rural co-operatives in Southwest Paraná, Brazil - Leomara Battisti Telles; Luciano Medina Macedo; Juliana Vitória Messias Bittencourt (Economies, 2024)
The maintenance of a satisfactory quality of life in rural areas is fundamental for sustainable development. One of the ways to improve quality of life indicators is through the gathering of rural workers in solidarity economy organizations as these enterprises aim to integrate development with economic, social, and environmental sustainability. Because solidarity economy organizations have a robust social purpose, their performance must be evaluated based on both social and financial indicators. The objective of this article is to propose a performance evaluation model for rural solidarity economy enterprises, aiming to support decision making in these enterprises based on multicriteria decision analysis (MCDA), particularly the ELECTRE-TRI methodology. In order to demonstrate the applicability of the developed model and to perform sensitivity analyses, the model was applied to a group of eight family agriculture co-operatives in the southwest state of Paraná, Brazil. All the participating co-ops were considered part of the solidarity economy, and they served 2500 rural producer families across at least 15 municipalities. The results showed the applicability and stability of the model, enabling us to identify the dimensions in which each co-op should concentrate their efforts to improve not only their performance but also the outcomes for the farmers that they serve. Based on these results, organizational and improvement activities can be developed and implemented. This analysis contributes to economic and social indicators by offering improvement strategies for the professionalization and strategic management of RSEEs, thus strengthening these enterprises and, consequently, family agriculture.
Keywords: 330; co-operatives; ELECTRE TRI; family agriculture; multicriteria decision analysis; performance evaluation; solidarity economy